Optimization of ball milling process for Ti(C,N)-based cermets: Microstructure and properties analysis via Taguchi method - Liu, Tianzhu; Liu, Gang; Peng, Yingbiao; Li, Yinzhi; Tan, Zhenyu; Yan, Lianwu (Ceramics international, 2025)
The particle sizes of raw materials and their subsequent solid-solution behavior play an important role in the evolution of typical “core-rim” structure, further affecting the properties of Ti(C,N)-based cermets. In this study, three parameters during ball-milling process, including Ti(C,N) and WC particle sizes, and ball-milling time were investigated and optimized by using a Taguchi approach. The solid-solution behavior during solid-state sintering process was systematically studied based on thermodynamic calculations and experimental characterizations, including O, N and C analysis, X-ray diffraction (XRD) and scanning electron microscopy (SEM). The main effect plots of ball-milling processing parameters on the density, black-core and core-rim structure grain sizes, magnetic properties (Com and Hc), hardness (HV10), fracture toughness (KIC) and flexural strength (TRS) were applied to determine the optimal level of each parameter. The results indicated that finer particle size promoted the solid-solution process, thereby reducing the N content and increasing the ratio of rim phase. Interestingly, prolonged ball-milling time can also accelerate the solid-solution process, however, resulting in higher N content due to the premature closure of open pores under the effect of ball-milling activation. Besides of ball-milling time, the grain sizes of black core and core-rim structures were strongly correlated with Ti(C,N) particle size, conversely with negligible influence of WC grain size. Based on Taguchi optimizations, T2.5-W0.7–48 and T1-W0.7-48, the combination of 2.5 and 1.0 μm Ti(C,N), 0.7 μm WC and 48 h milling time, achieved the best comprehensive properties. Among them, T2.5-W0.7-48 with better KIC may provide excellent chipping resistance, and T1-W0.7-48 with better TRS may provide excellent micro-chipping resistance at the cutting edge. Moreover, T1-W0.7-72 was ideal for wear-resistance applications, while T2.5-W0.7-24 for impact-resistance applications.